Characterization of PCL and Chitosan Nanoparticles as Carriers of Enoxaparin and Its Antithrombotic Effect in Animal Models of Venous Thrombosis. (23rd February 2017) - Prado, Lucas Bessa; Huber, Stephany Cares; Barnabé, Aline; Bassora, Fernanda Dutra Santiago; Paixão, Devanira Souza; Duran, Nelson; Annichino-Bizzacchi, Joyce Maria
Abstract : This study was based on the preparation, characterization, and animal in vivo experiments performed to evaluate nanoparticles of poly(ɛ-caprolactone) (PCL) and chitosan as carriers of enoxaparin. The nanoparticles were characterized and presented satisfactory results in terms of size, polydispersity, and encapsulation efficiency. Anticoagulant activity of the nanoparticles was maintained for 14 hours when the administration was subcutaneous; however no activity was observed after oral administration. There was a significant reduction in thrombus size, in vivo, for both free and encapsulated enoxaparin in comparison with the control group after subcutaneous administration. Oral administration results however were indifferent. In conclusion, the double emulsion method w/o/w was efficient for enoxaparin encapsulation, producing spherical nanoparticles with high encapsulation efficiency. For in vivo studies, the encapsulated enoxaparin showed a sustained anticoagulant activity for a higher period of time compared to free enoxaparin, with an antithrombotic effect when administered subcutaneously.